2001
DOI: 10.1128/jb.183.18.5453-5458.2001
|View full text |Cite
|
Sign up to set email alerts
|

Recombinational Transfer of 100-Kilobase Genomic DNA to Plasmid in Bacillus subtilis 168

Abstract: Transformation of Bacillus subtilis by a plasmid requires a circular multimeric form. In contrast, linearized plasmids can be circularized only when homologous sequences are present in the host genome. A recombinational transfer system was constructed with this intrinsic B. subtilis recombinational repair pathway. The vector, pGETS103, a derivative of the -type replicating plasmid pTB19 of thermophilic Bacillus, had the full length of Escherichia coli plasmid pBR322. A multimeric form of pGETS103 yielded tetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3
2

Relationship

5
4

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 19 publications
2
38
0
1
Order By: Relevance
“…Those findings indicated that appropriately edited DNA cloned in the BGM vector yields DNA suitable for use in different research undertakings. The retrieval of megacloned DNA by the recovery system (14,36) or the genome surgery system (37) renders the BGM vector a tool with which technical breakthroughs may be achieved.…”
Section: Comparison Of Our Cloning Vehicle and Conventional Cloning Vmentioning
confidence: 99%
“…Those findings indicated that appropriately edited DNA cloned in the BGM vector yields DNA suitable for use in different research undertakings. The retrieval of megacloned DNA by the recovery system (14,36) or the genome surgery system (37) renders the BGM vector a tool with which technical breakthroughs may be achieved.…”
Section: Comparison Of Our Cloning Vehicle and Conventional Cloning Vmentioning
confidence: 99%
“…The third method involves a yet more complicated genetic process referred to as Bacillus Recombinational Transfer (BReT) (Tsuge & Itaya, 2001;Kaneko et al, 2005). Indeed, BReT relies on homologous recombination in B. subtilis and should be as simple as the genetic disconnection procedure described above.…”
Section: Retrieval By Copying Segments Of the B Subtilis Genomementioning
confidence: 99%
“…1,2) This method, designated the B. subtilis Recombinational Transfer (BReT) method, shown in Fig. 1, presents no theoretical problem of applicability to any genome region.…”
Section: Region Dependent Efficiency For Recombinational Transfer Of mentioning
confidence: 99%